PRELIMINARY SCREENING OF PLANT SPECIES THAT MAY BE USEFUL IN CONTROLLING DIARRHOEA IN PRODUCTION LIVESTOCK. - Komape, N. P. M.; McGaw, L. J.; Eloff, J. N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
There are many causes of diarrhoea in production livestock. Some of these causes are infections with microorganisms such as Salmonella typhimurium, Clostridium perfringens and Escherichia coli. Administration of antibiotic growth promoters (AGPs) as feed additives to these animals helps reduce the occurrence of these microorganisms, and hence counteracts diarrhoea. There are many disadvantages to the use of AGPs, including the development of bacterial resistance with prolonged use. Therefore, there is a need to develop AGPs that are cheaper, of natural origin, effective in preventing diarrhoea in production livestock, and not associated with development of resistance. Leaves of fourteen plant species, Indigophera cylindrica, Rhoicissus sp., Ziziphus rivularis, Heteropyxis natalensis, Syzygium legatti, Faidherbia albida, Sapium integerrium, Thespesia acutiloba, Tamarindus indica, Polycias fulva, Acridocarpus natalitius, Ficus sur, Grewia occidentalis and Englerophytum magalismontanum were selected based on their activity against Escherichia coli in a broad preliminary screening in the Phytomedicine Laboratory. These plants were extracted using acetone and the plants were further screened for antibacterial activity using bioautographic and MIC methods against Salmonella typhimurium, Clostridium perfringens and Escherichia coli. The total activity of the plants was calculated using the mass extracted and the MIC value obtained. From the results obtained, H. natalensis had the best antibacterial activity against the three test microorganisms, followed by T. indica. Based on the profiles of the plants from literature searches and other criteria, including their traditional use,